FEEDBACK: DIFFERENT CONCEPTS AND PRACTICES IN A CULTURALLY DIFFERENT LEARNING ENVIRONMENT? STUDENTS’ PERCEPTIONS: Culturally Different Learning Environment - Malik, Ahsan; Kiran, Faiza; Farooq, Fareeha (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess students’ perceptions of feedback, regarding its understanding, and practices in a traditional undergraduate dental curriculum in Pakistan, where feedback was not part of a formal curriculum as a structured entity. Study Design: Qualitative-phenomenology. Place and Duration of Study: Rawal Institute of Health Sciences, Islamabad from Dec 2017 to May 2018. Methodology: Purposive sampling was done, and data was gathered using semi-structured, group interview of 16 BDS students. Data was organized using qualitative software package Atlas.ti 8.0 and analyzed using thematic framework analysis. Results: Feedback, though, being practiced by faculty, was not identify as feedback by students. They did not appreciate it as an essential skillset for learning and performance. Though, conceptions of students regarding this phenomenon varied, five emergent themes displayed the essence of the phenomenon in this learning environment: 1) understanding ‘feedback’ through participants’ response, 2) highly variant experiences of information exchange, 3) modes and forms of feedback, 4) factors affecting feedback and 5) methods achieving learning progression. Conclusion: Our students were devoid of formally instituted feedback practices, so they were unable to identify it as ‘feedback’. Wide range of contradictory and many negative experiences of participants indicated that formal training in feedback and its systematic use might improve students’ experiences. Keywords: , , , , , .